Late infectious endocarditis of surgical patch closure of atrial septal defects diagnosed by 18F-fluorodeoxyglucose gated cardiac computed tomography (18F-FDG-PET/CT): a case report. (December 2016) - Honnorat, Estelle; Seng, Piseth; Riberi, Alberto; Habib, Gilbert; Stein, Andreas
Abstract Background In contrast to percutaneous atrial septal occluder device, surgical patch closure of atrial defects was known to be no infective endocarditis risk. Case presentation We herein report the first case of late endocarditis of surgical patch closure of atrial septal defects occurred at 47-year after surgery. On September 2014, a 56-year-old immunocompetent French Caucasian man was admitted into the Emergency Department for 3-week history of headache, acute decrease of psychomotor performance and fever at 40 °C. The diagnosis has been evoked during his admission for the management of a brain abscess and confirmed using 18F-fluorodeoxyglucose gated cardiac computed tomography (18F-FDG-PET/CT). Bacterial cultures of surgical deep samples of brain abscess were positive forStreptococcus intermedius andAggregatibacter aphrophilus as identified by the matrix-assisted laser desorption/ionization-time of flight (MALDI-TOF) mass spectrometry and confirmed with 16S rRNA gene sequencing. The patient was treated by antibiotics for 8 weeks and surgical patch closure removal. Conclusions In summary, late endocarditis on surgical patch and on percutaneous atrial septal occluder device of atrial septal defects is rare. Cardiac imaging by the 18F-fluorodeoxyglucose gated cardiac computed tomography (18F-FDG-PET/CT) could improve the diagnosis and care endocarditis on surgical patch closure of atrial septal defects while transthoracic and transesophageal echocardiography remained difficult to interpret.